2021
DOI: 10.3389/fmolb.2021.653262
|View full text |Cite|
|
Sign up to set email alerts
|

Active-Site Models of Streptococcus pyogenes Cas9 in DNA Cleavage State

Abstract: CRISPR-Cas9 is a powerful tool for target genome editing in living cells. Significant advances have been made to understand how this system cleaves target DNA. HNH is a nuclease domain, which shares structural similarity with the HNH endonuclease characterzied by a beta-beta-alpha-metal fold. Therefore, based on one- and two-metal-ion mechanisms, homology modeling and molecular dynamics (MD) simulation are suitable tools for building an atomic model of Cas9 in the DNA cleavage state. Here, by modeling and MD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…An atomic model of the cleavage state of the SpCas9-sgRNA-DNA complex was built by using comparative modeling and molecular dynamics simulation. This model was used as a guide for engineering of a variant with reduced off-target effects …”
Section: Crispr-cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…An atomic model of the cleavage state of the SpCas9-sgRNA-DNA complex was built by using comparative modeling and molecular dynamics simulation. This model was used as a guide for engineering of a variant with reduced off-target effects …”
Section: Crispr-cas9mentioning
confidence: 99%
“…This model was used as a guide for engineering of a variant with reduced off-target effects. 79 Molecular dynamics calculations also provide insights regarding the off-target effects of CRISPR-Cas9 systems. MD simulations revealed that mismatched pairs in the DNA that are distal to the PAM motif induce extended opening of the RNA:DNA complex and result in altered interactions with the protein, whereas upstream mismatches are tolerated.…”
Section: ■ Crispr-cas9mentioning
confidence: 99%
“…While the size of the Cas9 HNH domain is ideal for nuclear magnetic resonance (NMR) studies, it limits our ability to directly address the catalytic mechanism of this enzyme, which would require the binding of nucleic acid substrates as well as interactions with many other protein domains within the enzyme that are essential for the high-affinity binding of nucleic acids. Nonetheless, our NMR-based studies of the Cas9 HNH domain should be complementary to many other biophysical and biochemical studies of the intact Cas9 enzyme, including cryo-electron microscopy. …”
Section: Introductionmentioning
confidence: 99%
“…However, the exact positions of the catalytic Mg 2+ were unresolved due to poor resolution in the electron density map. The RuvC domain contains four catalytically important residues, D10, E762, H983, and D986 (Figure ), coordinated with two Mg 2+ ions (position modeled) for cleavage of the ntDNA. ,, H983 was proposed to act as a Lewis base for DNA cleavage that coordinates with water for nucleophilic attack of the scissile phosphate . However, a single Mg 2+ (position modeled) coordinated with the catalytic residues of the HNH domain (D839, H840, and N863, Figure ) facilitates the tDNA cleavage. , H840 serves as a Lewis base, activating the water molecule for nucleophilic attack on the phosphate group of tDNA .…”
Section: The Crispr/cas9 Systemmentioning
confidence: 99%
“…•cryo-EM 78,89 •proposed activation pathway of the HNH domain proposed to act as a Lewis base for DNA cleavage that coordinates with water for nucleophilic attack of the scissile phosphate. 19 However, a single Mg 2+ (position modeled) coordinated with the catalytic residues of the HNH domain (D839, H840, and N863, Figure 6) facilitates the tDNA cleavage.…”
Section: The Crispr/cas9 Systemmentioning
confidence: 99%